The value of \[{{\sec }^{2}}\theta +{{\operatorname{cosec}}^{2}}\theta \] is equal to
\[\left( a \right){{\tan }^{2}}\theta +{{\cot }^{2}}\theta \]
\[\left( b \right){{\sec }^{2}}\theta .{{\operatorname{cosec}}^{2}}\theta \]
\[\left( c \right)\sec \theta .\operatorname{cosec}\theta \]
\[\left( d \right){{\sin }^{2}}\theta .{{\cos }^{2}}\theta \]
\[\left( e \right)1\]
Answer
Verified
483k+ views
Hint: We have to evaluate the value of \[{{\sec }^{2}}\theta +{{\operatorname{cosec}}^{2}}\theta \] first and we use reciprocal identity \[\sec \theta =\dfrac{1}{\cos \theta }\] and \[\operatorname{cosec}\theta =\dfrac{1}{\sin \theta }.\] Then we add the term by using the identity \[{{\cos }^{2}}\theta +{{\sin }^{2}}\theta =1\] and in the end we again use the reciprocal identity to get the solution in standard form as asked.
Complete step-by-step answer:
We have to find the value of \[{{\operatorname{cosec}}^{2}}\theta +{{\sec }^{2}}\theta .\] We know that \[\operatorname{cosec}\theta =\dfrac{1}{\sin \theta },\] and we have seen that \[\sec \theta =\dfrac{1}{\cos \theta }.\]
Using this in \[{{\operatorname{cosec}}^{2}}\theta +{{\sec }^{2}}\theta ,\] we have,
\[{{\operatorname{cosec}}^{2}}\theta +{{\sec }^{2}}\theta ={{\left( \dfrac{1}{\sin \theta } \right)}^{2}}+{{\left( \dfrac{1}{\cos \theta } \right)}^{2}}\]
As \[{{\left( \theta \right)}^{2}}={{\theta }^{2}}\] we get,
\[\Rightarrow {{\operatorname{cosec}}^{2}}\theta +{{\sec }^{2}}\theta =\dfrac{1}{{{\sin }^{2}}\theta }+\dfrac{1}{{{\cos }^{2}}\theta }\]
Now we take the LCM of \[{{\sin }^{2}}\theta \] and \[{{\cos }^{2}}\theta \] to add the terms
\[\Rightarrow \dfrac{{{\cos }^{2}}\theta +{{\sin }^{2}}\theta }{{{\sin }^{2}}\theta {{\cos }^{2}}\theta }\]
As we know that \[{{\cos }^{2}}\theta +{{\sin }^{2}}\theta =1\] we get,
\[\Rightarrow \dfrac{1}{{{\sin }^{2}}\theta {{\cos }^{2}}\theta }\]
We also know that \[{{a}^{2}}={{\left( a \right)}^{2}}\]
\[\Rightarrow {{\left( \dfrac{1}{\sin \theta } \right)}^{2}}{{\left( \dfrac{1}{\cos \theta } \right)}^{2}}\]
Again using the reciprocal identity, we know that,
\[\dfrac{1}{\sin \theta }=\operatorname{cosec}\theta \]
\[\dfrac{1}{\cos \theta }=sec\theta \]
We get,
\[={{\left( \operatorname{cosec}\theta \right)}^{2}}.{{\left( \sec \theta \right)}^{2}}\]
\[={{\operatorname{cosec}}^{2}}\theta .{{\sec }^{2}}\theta \]
So, the correct answer is “Option B”.
Note: We can check how other options are not correct solutions. Let us take \[\theta ={{45}^{\circ }}.\]
\[\left( a \right){{\tan }^{2}}\theta +{{\cot }^{2}}\theta ={{\tan }^{2}}{{45}^{\circ }}+{{\cot }^{2}}{{45}^{\circ }}\]
We know that \[\tan {{45}^{\circ }}=\cot {{45}^{\circ }}=1.\]
\[\Rightarrow 1+1=2\]
While at \[\theta ={{45}^{\circ }},\]
\[{{\sec }^{2}}\theta +{{\operatorname{cosec}}^{2}}\theta ={{\sec }^{2}}{{45}^{\circ }}+{{\operatorname{cosec}}^{2}}{{45}^{\circ }}\]
We know that \[\sec {{45}^{\circ }}=\cos {{45}^{\circ }}=\sqrt{2}\]
\[\Rightarrow {{\sec }^{2}}\theta +{{\operatorname{cosec}}^{2}}\theta ={{\left( \sqrt{2} \right)}^{2}}+{{\left( \sqrt{2} \right)}^{2}}\]
\[\Rightarrow {{\sec }^{2}}\theta +{{\operatorname{cosec}}^{2}}\theta =2+2\]
\[\Rightarrow {{\sec }^{2}}\theta +{{\operatorname{cosec}}^{2}}\theta =4........\left( i \right)\]
Therefore, we get that \[{{\sec }^{2}}\theta +{{\operatorname{cosec}}^{2}}\theta \] is not equal to \[{{\tan }^{2}}\theta +{{\cot }^{2}}\theta .\]
\[\left( c \right)\sec \theta .\operatorname{cosec}\theta \]
At \[\theta ={{45}^{\circ }},\] we know that,
\[\Rightarrow \sec {{45}^{\circ }}=\operatorname{cosec}{{45}^{\circ }}=\sqrt{2}\]
So, we get,
\[\sec \theta .\operatorname{cosec}\theta =\sqrt{2}\times \sqrt{2}\]
\[\Rightarrow \sec \theta .\operatorname{cosec}\theta =2\]
Again using (i) and the above value, we get, \[\sec \theta .\operatorname{cosec}\theta \] is not equal to \[{{\sec }^{2}}\theta +{{\operatorname{cosec}}^{2}}\theta .\]
\[\left( d \right){{\sin }^{2}}\theta .{{\cos }^{2}}\theta \]
At \[\theta ={{45}^{\circ }},\] we get,
\[{{\sin }^{2}}\theta .{{\cos }^{2}}\theta ={{\sin }^{2}}{{45}^{\circ }}.{{\cos }^{2}}{{45}^{\circ }}\]
As, \[\sin {{45}^{\circ }}=\cos {{45}^{\circ }}=\dfrac{1}{\sqrt{2}},\] we get,
\[\Rightarrow {{\sin }^{2}}\theta .{{\cos }^{2}}\theta ={{\left( \dfrac{1}{\sqrt{2}} \right)}^{2}}\times {{\left( \dfrac{1}{\sqrt{2}} \right)}^{2}}\]
\[\Rightarrow {{\sin }^{2}}\theta .{{\cos }^{2}}\theta =\dfrac{1}{2}\times \dfrac{1}{2}\]
Solving further, we get, \[{{\sin }^{2}}\theta .{{\cos }^{2}}\theta =\dfrac{1}{4}\] at \[\theta ={{45}^{\circ }}.\]
So using (i) and above, we again get, \[{{\sin }^{2}}\theta .{{\cos }^{2}}\theta \] is not equal to \[{{\sec }^{2}}\theta +{{\operatorname{cosec}}^{2}}\theta .\]
(e) 1
At \[\theta ={{45}^{\circ }},\] 1 is always 1.
But from (i), we have
\[{{\sec }^{2}}\theta +{{\operatorname{cosec}}^{2}}\theta =4\] at \[\theta ={{45}^{\circ }}.\]
So, 1 is not equal to \[{{\sec }^{2}}\theta +{{\operatorname{cosec}}^{2}}\theta .\]
So, 1 is not equal to \[{{\sec }^{2}}\theta +{{\operatorname{cosec}}^{2}}\theta .\]
Complete step-by-step answer:
We have to find the value of \[{{\operatorname{cosec}}^{2}}\theta +{{\sec }^{2}}\theta .\] We know that \[\operatorname{cosec}\theta =\dfrac{1}{\sin \theta },\] and we have seen that \[\sec \theta =\dfrac{1}{\cos \theta }.\]
Using this in \[{{\operatorname{cosec}}^{2}}\theta +{{\sec }^{2}}\theta ,\] we have,
\[{{\operatorname{cosec}}^{2}}\theta +{{\sec }^{2}}\theta ={{\left( \dfrac{1}{\sin \theta } \right)}^{2}}+{{\left( \dfrac{1}{\cos \theta } \right)}^{2}}\]
As \[{{\left( \theta \right)}^{2}}={{\theta }^{2}}\] we get,
\[\Rightarrow {{\operatorname{cosec}}^{2}}\theta +{{\sec }^{2}}\theta =\dfrac{1}{{{\sin }^{2}}\theta }+\dfrac{1}{{{\cos }^{2}}\theta }\]
Now we take the LCM of \[{{\sin }^{2}}\theta \] and \[{{\cos }^{2}}\theta \] to add the terms
\[\Rightarrow \dfrac{{{\cos }^{2}}\theta +{{\sin }^{2}}\theta }{{{\sin }^{2}}\theta {{\cos }^{2}}\theta }\]
As we know that \[{{\cos }^{2}}\theta +{{\sin }^{2}}\theta =1\] we get,
\[\Rightarrow \dfrac{1}{{{\sin }^{2}}\theta {{\cos }^{2}}\theta }\]
We also know that \[{{a}^{2}}={{\left( a \right)}^{2}}\]
\[\Rightarrow {{\left( \dfrac{1}{\sin \theta } \right)}^{2}}{{\left( \dfrac{1}{\cos \theta } \right)}^{2}}\]
Again using the reciprocal identity, we know that,
\[\dfrac{1}{\sin \theta }=\operatorname{cosec}\theta \]
\[\dfrac{1}{\cos \theta }=sec\theta \]
We get,
\[={{\left( \operatorname{cosec}\theta \right)}^{2}}.{{\left( \sec \theta \right)}^{2}}\]
\[={{\operatorname{cosec}}^{2}}\theta .{{\sec }^{2}}\theta \]
So, the correct answer is “Option B”.
Note: We can check how other options are not correct solutions. Let us take \[\theta ={{45}^{\circ }}.\]
\[\left( a \right){{\tan }^{2}}\theta +{{\cot }^{2}}\theta ={{\tan }^{2}}{{45}^{\circ }}+{{\cot }^{2}}{{45}^{\circ }}\]
We know that \[\tan {{45}^{\circ }}=\cot {{45}^{\circ }}=1.\]
\[\Rightarrow 1+1=2\]
While at \[\theta ={{45}^{\circ }},\]
\[{{\sec }^{2}}\theta +{{\operatorname{cosec}}^{2}}\theta ={{\sec }^{2}}{{45}^{\circ }}+{{\operatorname{cosec}}^{2}}{{45}^{\circ }}\]
We know that \[\sec {{45}^{\circ }}=\cos {{45}^{\circ }}=\sqrt{2}\]
\[\Rightarrow {{\sec }^{2}}\theta +{{\operatorname{cosec}}^{2}}\theta ={{\left( \sqrt{2} \right)}^{2}}+{{\left( \sqrt{2} \right)}^{2}}\]
\[\Rightarrow {{\sec }^{2}}\theta +{{\operatorname{cosec}}^{2}}\theta =2+2\]
\[\Rightarrow {{\sec }^{2}}\theta +{{\operatorname{cosec}}^{2}}\theta =4........\left( i \right)\]
Therefore, we get that \[{{\sec }^{2}}\theta +{{\operatorname{cosec}}^{2}}\theta \] is not equal to \[{{\tan }^{2}}\theta +{{\cot }^{2}}\theta .\]
\[\left( c \right)\sec \theta .\operatorname{cosec}\theta \]
At \[\theta ={{45}^{\circ }},\] we know that,
\[\Rightarrow \sec {{45}^{\circ }}=\operatorname{cosec}{{45}^{\circ }}=\sqrt{2}\]
So, we get,
\[\sec \theta .\operatorname{cosec}\theta =\sqrt{2}\times \sqrt{2}\]
\[\Rightarrow \sec \theta .\operatorname{cosec}\theta =2\]
Again using (i) and the above value, we get, \[\sec \theta .\operatorname{cosec}\theta \] is not equal to \[{{\sec }^{2}}\theta +{{\operatorname{cosec}}^{2}}\theta .\]
\[\left( d \right){{\sin }^{2}}\theta .{{\cos }^{2}}\theta \]
At \[\theta ={{45}^{\circ }},\] we get,
\[{{\sin }^{2}}\theta .{{\cos }^{2}}\theta ={{\sin }^{2}}{{45}^{\circ }}.{{\cos }^{2}}{{45}^{\circ }}\]
As, \[\sin {{45}^{\circ }}=\cos {{45}^{\circ }}=\dfrac{1}{\sqrt{2}},\] we get,
\[\Rightarrow {{\sin }^{2}}\theta .{{\cos }^{2}}\theta ={{\left( \dfrac{1}{\sqrt{2}} \right)}^{2}}\times {{\left( \dfrac{1}{\sqrt{2}} \right)}^{2}}\]
\[\Rightarrow {{\sin }^{2}}\theta .{{\cos }^{2}}\theta =\dfrac{1}{2}\times \dfrac{1}{2}\]
Solving further, we get, \[{{\sin }^{2}}\theta .{{\cos }^{2}}\theta =\dfrac{1}{4}\] at \[\theta ={{45}^{\circ }}.\]
So using (i) and above, we again get, \[{{\sin }^{2}}\theta .{{\cos }^{2}}\theta \] is not equal to \[{{\sec }^{2}}\theta +{{\operatorname{cosec}}^{2}}\theta .\]
(e) 1
At \[\theta ={{45}^{\circ }},\] 1 is always 1.
But from (i), we have
\[{{\sec }^{2}}\theta +{{\operatorname{cosec}}^{2}}\theta =4\] at \[\theta ={{45}^{\circ }}.\]
So, 1 is not equal to \[{{\sec }^{2}}\theta +{{\operatorname{cosec}}^{2}}\theta .\]
So, 1 is not equal to \[{{\sec }^{2}}\theta +{{\operatorname{cosec}}^{2}}\theta .\]
Recently Updated Pages
Glucose when reduced with HI and red Phosphorus gives class 11 chemistry CBSE
The highest possible oxidation states of Uranium and class 11 chemistry CBSE
Find the value of x if the mode of the following data class 11 maths CBSE
Which of the following can be used in the Friedel Crafts class 11 chemistry CBSE
A sphere of mass 40 kg is attracted by a second sphere class 11 physics CBSE
Statement I Reactivity of aluminium decreases when class 11 chemistry CBSE
Trending doubts
10 examples of friction in our daily life
The correct order of melting point of 14th group elements class 11 chemistry CBSE
Difference Between Prokaryotic Cells and Eukaryotic Cells
One Metric ton is equal to kg A 10000 B 1000 C 100 class 11 physics CBSE
State and prove Bernoullis theorem class 11 physics CBSE
What organs are located on the left side of your body class 11 biology CBSE